This answer is restricted. Please login to view the answer of this question.

Login NowLet us suppose,

p = x and y are odd

q = xy is odd

i.e. p → q

**First Case:** p → q (direct proof)

If x and y are odd then xy is odd. By the definition of odd integers, Ǝ integers a, b.

x = 2a + 1 and y = 2b + 1

xy = (2a + 1) (2b + 1)

= 4ab + 2a + 2b + 1

= 2(2ab + a + b) + 1

= 2c + 1, for some integer c

Here, x is also odd by direct proof

**Second Case:**** **¬ q → ¬ p (indirect proof)

The product xy is odd if and only if x and y are odd.

p = product xy is odd

q = x and y are odd

Let us suppose, x and y are even

Now, We prove: ¬ q → ¬ p

By definition of even integers Ǝ integers a, b

x = 2a and y = 2b

xy = 2a × 2b

= 4ab

= 2 (2ab)

= 2c, for some integers

So, xy is even

Hence, by contraposition we can say xy is odd

Therefore, By direct proof and contraposition, the product xy is odd if and only if x and y is odd.

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

HAMROCSIT.COM

## Discussion